Political Instability and Its Consequences for Economic Growth in Ethiopia: A Time Series Analysis - Adisu Ayal, Betselot; Bamelak Bishaw, Esayas; Molla Aynalem, Mulugeta; Yirga Bekalu, Kassa (Journal of Economics and Administrative Sciences, 2024)
Political instability in Ethiopia is highly destructive to the country's economic development and hinders progress across multiple sectors. Thus, this study investigates the impacts of political instability on economic growth in Ethiopia from 2017 to 2023. The study employs ARIMA modeling for time series analysis and OLS regression to estimate the relationship between political instability and GDP growth while considering other economic indicators such as inflation, FDI, and government expenditure. For this purpose, the necessary secondary data is collected from WB, IMF, EIA, and MoFED, covering the period from 2017 to 2023. The empirical results reveal a significant negative correlation between political instability and economic growth in Ethiopia. The regression model indicated that higher levels of political instability are associated with lower GDP growth rates, confirming the detrimental effects of instability on economic performance. While other economic factors, such as lagged real GDP per capita and FDI, have a significant and positive effect on economic growth, government spending significantly negatively affects growth in Ethiopia.Furthermore, the result of the robustness checks model specifications were tested: the original model, a model with alternatives, and a model that excluded outliers in measures of political instability. In all cases, the coefficient of political instability is consistently negative, indicating the detrimental impact on economic growth. To mitigate these adverse impacts, it is recommended that the Ethiopian government and policymakers prioritize inclusive dialogue, political reconciliation, and institutional reforms.